Hormonal Regulation of Diapause and Development in Nematodes, Insects, and Fishes - Karp, Xantha (Frontiers in Ecology and Evolution, 2021)
Diapause is a state of developmental arrest adopted in response to or in anticipation of environmental conditions that are unfavorable for growth. In many cases, diapause is facultative, such that animals may undergo either a diapause or a non-diapause developmental trajectory, depending on environmental cues. Diapause is characterized by enhanced stress resistance, reduced metabolism, and increased longevity. The ability to postpone reproduction until suitable conditions are found is important to the survival of many animals, and both vertebrate and invertebrate species can undergo diapause. The decision to enter diapause occurs at the level of the whole animal, and thus hormonal signaling pathways are common regulators of the diapause decision. Unlike other types of developmental arrest, diapause is programmed, such that the diapause developmental trajectory includes a pre-diapause preparatory phase, diapause itself, recovery from diapause, and post-diapause development. Therefore, developmental pathways are profoundly affected by diapause. Here, I review two conserved hormonal pathways, insulin/IGF signaling (IIS) and nuclear hormone receptor signaling (NHR), and their role in regulating diapause across three animal phyla. Specifically, the species reviewed are Austrofundulus limnaeus and Nothobranchius furzeri annual killifishes, Caenorhabditis elegans nematodes, and insect species including Drosophila melanogaster, Culex pipiens, and Bombyx mori. In addition, the developmental changes that occur as a result of diapause are discussed, with a focus on how IIS and NHR pathways interact with core developmental pathways in C. elegans larvae that undergo diapause.